Hospitalizations, costs, and mortality among infants with critical congenital heart disease: How important is timely detection?. Issue 10 (2nd September 2013) - Peterson, Cora; Dawson, April; Grosse, Scott D.; Riehle‐Colarusso, Tiffany; Olney, Richard S.; Tanner, Jean Paul; Kirby, Russell S.; Correia, Jane A.; Watkins, Sharon M.; Cassell, Cynthia H.
<x xml:space="preserve">Abstract</x> BACKGROUND Critical congenital heart disease (CCHD) was recently added to the U.S. Recommended Uniform Screening Panel for newborns. States considering screening requirements may want more information about the potential impact of screening. This study examined potentially avoidable mortality among infants with late detected CCHD and assessed whether late detection was associated with increased hospital resource use during infancy. METHODS This was a state‐wide, population‐based, observational study of infants with CCHD (n = 3603) born 1998 to 2007 identified by the Florida Birth Defects Registry. We examined 12 CCHD conditions that are targets of newborn screening. Late detection was defined as CCHD diagnosis after the birth hospitalization. Deaths potentially avoidable through screening were defined as those that occurred outside a hospital following birth hospitalization discharge and those that occurred within 3 days of an emergency readmission. RESULTS For 23% (n = 825) of infants, CCHD was not detected during the birth hospitalization. Death occurred among 20% (n = 568/2, 778) of infants with timely detected CCHD and 8% (n = 66/825) of infants with late detected CCHD, unadjusted for clinical characteristics. Potentially preventable deaths occurred in 1.8% (n = 15/825) of infants with late detected CCHD (0.4% of all infants with CCHD). In multivariable models adjusted for selected characteristics, late CCHD detection was significantly associated with 52% more admissions, 18% more hospitalized days, and 35% higher inpatient costs during infancy. CONCLUSION Increased CCHD detection at birth hospitals through screening may lead to decreased hospital costs and avoid some deaths during infancy. Additional studies conducted after screening implementation are needed to confirm these findings. Birth Defects Research (Part A) 97:664–672, 2013. © 2013 Wiley Periodicals, Inc.